ANALISIS PRINSIP AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN DANA BOS PADA UPT SDI 54 KEPULAUAN SELAYAR - Rusman .; Muhammad Fahreza W (STKIP Pembangunan Indonesia Makassar, 2022)
This study aims to determine the application of the principles of accountability and transparency in the management of BOS funds at UPT SDI 54 Selayar Islands. The research method is descriptive qualitative with an interactive analysis model. This research was conducted at UPT SDI 54 Selayar Islands. Primary data sources were obtained through an interview process with competent parties, namely the principal and the BOS treasurer. While secondary data obtained through observation from third parties or supporting documents and documentation related to this research. The results show that, 1) The principle of accountability in the management of BOS funds at UPT SDI 54 Selayar Islands has been implemented well. This can be seen in the form of an accountability report for the use of BOS funds in the form of a report that is deposited by the school to the local education office. 2) The principle of transparency in the management of BOS funds at UPT SDI 54 Selayar Islands has been well implemented. With the disclosure of information, starting from the planning for the preparation of the RAPBS with the BOS management team to the presentation of the use of BOS funds and their realization which was posted on the school information board. Keywords: Accountability, Transparency, and Management of BOS Funds